2014
DOI: 10.1111/apt.12758
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: the beneficial effects of VSL#3 in obese children with non‐alcoholic steatohepatitis

Abstract: SUMMARY Background Gut microbiota modifiers may have beneficial effects of non-alcoholic fatty liver disease (NAFLD) but randomised controlled trials (RCT) are lacking in children. Aim We performed a double-blind RCT of VSL#3 vs. placebo in obese children with biopsy-proven NAFLD. Methods Of 48 randomised children, 44 (22 VSL#3 and 22 placebo) completed the study. The main outcome was the change in fatty liver severity at 4 months as detected by ultrasonography. Secondary outcomes were the changes in trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
308
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(326 citation statements)
references
References 49 publications
9
308
0
9
Order By: Relevance
“…A few trials have demonstrated the beneficial effect of some probiotics in nonalcoholic fatty liver disease [16].…”
Section: Resultsmentioning
confidence: 99%
“…A few trials have demonstrated the beneficial effect of some probiotics in nonalcoholic fatty liver disease [16].…”
Section: Resultsmentioning
confidence: 99%
“…In RCT of VSL#3, "a mixture of eight probiotic strains" compare to placebo in overweight children with biopsy-proven NAFLD, administration of VSL#3 for 4 months significantly improves NAFLD in children (27).…”
Section: Discussionmentioning
confidence: 99%
“…Several proand prebiotics, such as VSL+3, MIYAIRI588, Bifidobacterium bifidum, and Lactobacillus plantarum, and antibiotics may have beneficial effects (143)(144)(145)(146)(147). Nonetheless, conflicting data on VSL+3 suggesting a detrimental effect on hepatic steatosis raise questions about interindividual differences in response to probiotics (148).…”
Section: Different Underlying Pathophysiologies and Therapeutic Implimentioning
confidence: 99%